SHON, a novel secreted protein, regulates epithelial–mesenchymal transition through transforming growth factor‐β signaling in human breast cancer cells. Issue 6 (11th August 2014) - Li, Lili; Liu, Dong‐Xu; Zhang, Na; Liang, Qian; Feng, Jingxin; Yao, Min; Liu, Jiwei; Li, Xiaoxue; Zhang, Yu; Lu, Jun; Huang, Baiqu
<x xml:space="preserve">Abstract</x> The epithelial–mesenchymal transition (EMT) is one of the main mechanisms contributing to the onset of cancer metastasis, and has proven to be associated with breast cancer progression. SHON is a novel secreted hominoid‐specific protein we have previously identified; it is specifically expressed in all human cancer cell lines tested and is oncogenic for human mammary carcinoma cells. Here, we show that ectopic overexpression of SHON in immortalized human mammary epithelial cells is sufficient for cells to acquire the mesenchymal traits, as well as the enhanced cell migration and invasion, along with the epithelial stem cell properties characterized by increased CD44high/CD24low subpopulation and mammosphere‐forming ability. Moreover, we demonstrate that SHON positively activates the autocrine transforming growth factor‐β (TGF‐β) pathway to contribute to EMT, while SHON itself is induced by TGF‐β in mammary epithelial cells. These data are in favor of a SHON‐TGFβ‐SHON‐positive feedback loop that regulates EMT program in breast cancer progression. Finally, examination of the human clinic breast cancer specimens reveals that tumor cells may extracellularly release SHON protein to promote the cancerization of surrounding cells. Together, our findings define an important function of SHON in regulation of EMT via TGF‐β signaling, which is closely associated with the invasive subtypes of human breast cancer.